A resource of validated and annotated gene fusions in cancer cell lines - Alamshahi,Arianna (2025)
In cancer cells, when two different genes are rearranged and joined, a fusion gene results and can act as a tumour driver. While many programs to predict fusion transcripts based on RNA-sequencing data do exist, the predictions contain many false positives without underlying genomic rearrangements. With the release of a new fusion validation pipeline to address this shortcoming, we have created a large dataset of validated and annotated gene fusions predicted by Arriba and STAR-Fusion from 328 cell lines of the publicly available Cancer Cell Line Encyclopedia. This dataset can act as a resource for the development of bioinformatic tools for fusion transcript detection and for design of functional studies or drug development.